Workers' Online Self-Disclosure Regarding Job Resignation on Twitter: A Netnographic Study - Karensa, Edo Nur; Silfia, Imamatul; Muttamimah, Laili; Selyna, Rafiidha (UI Scholars Hub, 2023)
Twitter, as a micro-blogging platform, is also utilized by workers in Indonesia to express themselves online, one of which is about the reason for resignation through the hashtag #EsokHariPastiResign pioneered by @hrdbacot. This study aims to examine what and how information about resignation is shared by workers, and what forms of self-disclosure are taken. The research method used netnography by analyzing 243 workers' tweets. The results show that workers have various reasons for resigning which are classified into eight aspects, namely social problems, supervisory, health, personal, pay, job security, professional growth, and personal value. Workers predominantly disclose themselves in forms of informational dimension with reflective and impulsive processes. We conclude that workers tend to disclose their job satisfaction at an informational level while still maintaining privacy boundaries on social media.